Protochlorophyll(ide) in a Blue-Green Alga - Myers, Jack (Plant Physiol, 1982)
During growth under far-red (>650 nm) light, Anacystis nidulans accumulates protochlorophyllide to concentrations about one-tenth of the chlorophyll. From whole cell fluorescence spectra, protochlorophyll(ide) was identified also in another blue-green, and in a red, alga grown in far-red light.